THE INFLUENCE OF ARTIFICIAL INTELLIGENCE ON THE EVOLUTION OF INTERNAL AUDIT METHODOLOGIES WITHIN THE FINANCIAL ENTITY (World Economics and Finance Bulletin, 2026)
This study seeks to determine the impact of artificial intelligence on the transformation of internal audit practices in commercial banks operating in Iraq, while also assessing the feasibility of using MindBridge AI technology and the human and material challenges that might hinder this process. The research relied on a sample of 152 individuals working in internal audit departments and related departments, using a questionnaire as a primary tool for gathering information, and a descriptive-analytic approach as a research methodology.
Keywords: Artificial intelligence; internal auditing; MindBridge